Antibacterial suture vs silk for the surgical removal of impacted lower third molars. A randomized clinical study - Sala-Pérez, Sergi (Med Oral Patol Oral Cir Bucal, 2016)
BACKGROUND: The aim of this study was to evaluate the clinical and microbiological impact of an antibacterial suture (Monocryl® Plus) in the surgical removal of I3M. MATERIAL AND METHODS: A “split-mouth”, prospective pilot clinical study was designed involving 20 patients programmed for the surgical removal of I3M. Each side was randomly sutured with Monocryl® Plus or silk suture and removed for microbiological study 72 hours and 7 days after surgery. Presence of SSI, wound bleeding and the degree of discomfort associated with each type of suture material (scored by means of a visual analog scale) were evaluated. The level of contamination of each material was observed under the scanning electron microscope. RESULTS: Wound bleeding upon suture removing was slightly greater after 72 hours and 7 days with black silk suture, though the differences were not statistically significant (p=0.752 and p=0.113, respectively). Patient discomfort was very similar with both types of suture material (p=0.861). Only one case of SSI was recorded with black silk suture after 72 hours. Microbiologically, the antibacterial suture showed a lesser presence of microorganisms (p<0.001, at 72h and p=0.033 at 7th day, respectively). The most common bacterial species included grampositive cocci (Streptococcus viridans group, Neisseria spp., Coagulasenegative Staphylococcus and Peptostreptococcus), gramnegative cocci (Veillonella), grampositive Bacilli (Lactobacillus), and gramnegative Bacilli (Prevotella). CONCLUSIONS: The greatest antibacterial effect of Monocryl Plus suture was observed after 72 hours. According to most authors, there is no doubt that this antibacterial suture can provide little safety in the control of SSI. Key words:Antibacterial suture, monocryl® plus, vicryl® plus, third molar surgery, postoperative infection, surgical site infection (SSI).